Data in support of dyslipidemia-associated alterations in B cell subpopulations frequency and phenotype during experimental atherosclerosis (2016)
ABSTARCT: Cardiovascular diseases are the most common cause of death in the world, atherosclerosis being its main underlying disease. Information about the role of B cells during atherosclerotic process is scarce, but both proatherogenic and atheroprotective properties have been described in the immunopathology of this disease. Frequency and phenotype of B cell subpopulations were studied in wild type and apolipoprotein-E-deficient (apoE / ) mice fed or not with high-fat diet (HFD), by flow cytometry. Here, we provide the information about the materials, methods, analysis and additional information related to our study published in Atherosclerosis